Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM122 - Ingo Grevemeyer; Lars H Rüpke; Yinuo Zhang; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM122 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 19.10.2023 – 09.11.2023 from Ponta Delgada (Azores) to Halifax (Canada) in the Central Atlantic Ocean. Data were recorded in the EEZs of Brasil and Cape Verde and outside. The aim of the swathmapping and magnetic survey of MSM122 is to test new hypotheses concerning the formation of transform faults at the Oceanographer OTF south of the Azores by using high-resolution seafloor topography and magnetic field data to obtain the magnetisation of the basement of both the OTF and fracture zones. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and are according to the FAIR principles.